2015
DOI: 10.7748/ns.29.35.40.e9929
|View full text |Cite
|
Sign up to set email alerts
|

Understanding non-compliance with hand hygiene practices

Abstract: Healthcare-associated infections (HCAIs) continue to be a challenge in developed and developing countries. Hand hygiene practice is considered to be the most effective strategy to prevent HCAIs, but healthcare workers' compliance is poor. Using a human factors perspective, this article explores elements that affect healthcare workers' hand hygiene compliance. Slips, lapses and mistakes can occur depending on the worker's skills and knowledge levels. Violations of protocols may also occur, and these may be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 0 publications
0
21
1
1
Order By: Relevance
“…Mistakes occur when the nurse is not consciously paying attention to the task and are more likely to be related to a lack of knowledge (knowledge-based errors), application of an incorrect rule, or incorrect application of a rule (rule-based errors) (Carayon 2012, Gluyas 2015. Gluyas (2015) examined hand hygiene compliance from the perspective of human factors, which include interactions between people's cognitive processes and their actions, the environment they are working in, and the tools they are using. This knowledge can provide an improved understanding of errors, as well as identifying strategies that will reduce them (Gluyas 2015).…”
Section: Hand Hygiene In Clinical Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Mistakes occur when the nurse is not consciously paying attention to the task and are more likely to be related to a lack of knowledge (knowledge-based errors), application of an incorrect rule, or incorrect application of a rule (rule-based errors) (Carayon 2012, Gluyas 2015. Gluyas (2015) examined hand hygiene compliance from the perspective of human factors, which include interactions between people's cognitive processes and their actions, the environment they are working in, and the tools they are using. This knowledge can provide an improved understanding of errors, as well as identifying strategies that will reduce them (Gluyas 2015).…”
Section: Hand Hygiene In Clinical Practicementioning
confidence: 99%
“…Gluyas (2015) examined hand hygiene compliance from the perspective of human factors, which include interactions between people's cognitive processes and their actions, the environment they are working in, and the tools they are using. This knowledge can provide an improved understanding of errors, as well as identifying strategies that will reduce them (Gluyas 2015). Suboptimal hand hygiene compliance can also occur through violations of accepted practice, where a healthcare worker deliberately decides not to follow procedures or requirements (Seo et al 2019).…”
Section: Hand Hygiene In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Está descrito que, cuando disminuye la vigilancia y las estrategias para mantener estas medidas, disminuye la adherencia y la tasa de infecciones vuelve a subir. [20][21][22] La alta rotación de personal, frecuente en las unidades de cuidados críticos, suma mayores dificultades a este desafío colectivo y hace necesario buscar nuevas estrategias de estímulo de manera permanente con el objetivo de lograr una mayor adherencia. El cambio fundamental consiste en lograr modificaciones en la cultura del personal de salud sobre la importancia de la higiene de manos y el cumplimiento de todos los puntos del programa por parte de todo el personal para alcanzar una reducción sostenida de las infecciones hospitalarias y continuar descendiendo las tasas de IAC actuales.…”
Section: Discussionunclassified
“…From a human factors perspective, noncompliance with IC practices may occur as a result of slips, lapses, mistakes and sometimes violations of protocols, which is a function of the healthcare workers' skills and knowledge levels (17). Some studies have shown that healthcare workers training is one of the strong predictors of compliance with IC standards (18).…”
Section: Discussionmentioning
confidence: 99%